2019
DOI: 10.48550/arxiv.1907.01864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

THz Surface Modes and Electron-Phonon Coupling in Bi$_2$Se$_3$(111)

Adrian Ruckhofer,
Davide Campi,
Martin Bremholm
et al.

Abstract: We present a combined experimental and theoretical study of the surface vibrational modes of the topological insulator (TI) Bi2Se3 with particular emphasis on the low-energy region below 10 meV that has been difficult to resolve experimentally. By applying inelastic helium atom scattering (HAS), the entire phonon dispersion was determined and compared with density functional perturbation theory (DFPT) calculations. The intensity of the phonon modes is dominated by a strong Rayleigh mode, in contrast to previou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Recent theoretical studies showed how the thermal attenuation of the He specular peak from metal surfaces, described by the Debye-Waller exponent, can be directly related to the e-ph coupling constant λ [18][19][20]. This approach has also been recently adapted to derive the e-ph coupling constant for the case of degenerated semiconductors and chalogenides [21][22][23]. This parameter, that allows to quanti fy the strength of the interaction between electrons and phonons at surfaces, is crucial to understand the scattering process of the surface-state electrons that can jeopardize the performance of 2D materials in possible applications [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical studies showed how the thermal attenuation of the He specular peak from metal surfaces, described by the Debye-Waller exponent, can be directly related to the e-ph coupling constant λ [18][19][20]. This approach has also been recently adapted to derive the e-ph coupling constant for the case of degenerated semiconductors and chalogenides [21][22][23]. This parameter, that allows to quanti fy the strength of the interaction between electrons and phonons at surfaces, is crucial to understand the scattering process of the surface-state electrons that can jeopardize the performance of 2D materials in possible applications [18,20].…”
Section: Introductionmentioning
confidence: 99%